The effect of fundamental analysis towards stock price movement: technology sectors in Malaysia / Nur Aqilah Daud - Daud, Nur Aqilah (Faculty of Business and Management, 2018)
The purpose of this research is to study the relationship between financial ratio and stock prices in Malaysia. A statistical examination to the prediction power of five financial ratios was tested and it depends on data of 8 companies distributed on one sector which is technology sector for the years 2015 to 2017. In this research, it will use quarterly data and the country that has been chosen is Malaysia. The independent variables in this research are ROA, PE, EPS, CR and DER. While for the dependent variable that has been selected is stock prices. Other than that, some tests have been used to obtain results for this research. The results showed that there is significant and insignificant effect on stock prices. The variables that shows the positive significant impact to stock prices are ROA and CR. The other variables other than ROA and CR shows the opposite results. This study concluded that it could rely on a set of financial ratios to predict stock prices, the decision maker or the investors can rely on financial analysis presented by the financial ratios when making financial and operational decisions.